KNOWLEDGE, ATTITUDES AND PRACTICE OF HUMAN PAPILLOMA VIRUS VACCINATION (HPV) AMONG WOMEN IN ANAMBRA STATE NIGERIA - Nkiru Camilla Emechebe; Adiola Sidikat Oyeleke (PEOPLE: International Journal of Social Sciences, 2025)
This study assessed the knowledge, attitude, and practice of Human Papillomavirus Vaccination among women of reproductive age in Anambra state. The study was premised against the increasing cases of cervical cancer, resulting from HPV infections, among female gender. With the introduction of the vaccine for HPV prevention in Nigeria in 2024, and subsequently including the vaccine in the routine immunization in Nigeria, it becomes pertinent to carry out this study. Aimed at finding out the proportion of women of reproductive age who were aware of HPV, as well as findings their attitudes and practices of HPV, this study was anchored on the Diffusion of Innovation theory. Using survey as the research design the study drew a sample of 400 women of reproductive age from public health institutions in each of the three zones in Anambra state. Structured questionnaire was the instrument used to garner data for the study. Data obtained were presented in simple frequency distribution tables and subsequently analyzed. Results revealed that a significant proportion of the respondents were aware of HPV vaccination. Results also revealed that a significant proportion of the respondents were ready to volunteer their daughters for the vaccination if it was free. Furthermore, results revealed that respondents demonstrated positive attitudes towards HPV. The study concluded that the public health campaigns on HPV should be sustained, with a view to improving the knowledge of HPV among younger age groups and regular screening among pregnant women. HPV vaccination has a relatively low coverage in Nigeria and the low Therefore, intense health campaign on HPV and HPV vaccine among women of reproductive age is notably recommended.